Results of experimental work connected with the development of a foreign language lexicon among students on the basis of the linguo-cultural approach (English) - Taleika, Karyna A. (Journal of the Belarusian State University. Philology, 2020)
The experimental verification of the results of the methodology for the development of a foreign language lexicon (English) among students on the basis of the linguo-cultural approach is described. The process of the development of a foreign language lexicon among students on the basis of the linguo-cultural approach; principles of the linguo-cultural approach, selection of a linguo-cultural vocabulary, system of exercises and tasks used for the development of a foreign language lexicon among students on the basis of the linguo-cultural approach are reveald. The experiment results show us that the application of the proposed methodology enhances the effectiveness of the development of a foreign language lexicon among students; develops the ability to communicate effectively in the modern multicultural world. The results of the research can be used for textbooks as well as in lecture courses on teaching methodology during the process of the development of a foreign language lexicon among students not only in English, but also in other foreign languages.
Keywords: foreign language lexicon; concept; cultural linguistics; linguo-cultural approach; cultural and social consciousness; speach etiquette; cross-cultural communication; experimental work